2005
DOI: 10.1128/jb.187.21.7267-7282.2005
|View full text |Cite
|
Sign up to set email alerts
|

An Expression-Driven Approach to the Prediction of Carbohydrate Transport and Utilization Regulons in theHyperthermophilic BacteriumThermotoga maritima

Abstract: Comprehensive analysis of genome-wide expression patterns during growth of the hyperthermophilic bacterium Thermotoga maritima on 14 monosaccharide and polysaccharide substrates was undertaken with the goal of proposing carbohydrate specificities for transport systems and putative transcriptional regulators. Saccharide-induced regulons were predicted through the complementary use of comparative genomics, mixedmodel analysis of genome-wide microarray expression data, and examination of upstream sequence pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
110
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 89 publications
(106 reference statements)
6
110
0
Order By: Relevance
“…Raw data were imported into SAS (SAS Institute), compiled, background-corrected, log 2 -transformed, and subjected to a mixed model of analysis of variance (SAS proc mixed) with two sequential linear models (44) outlined in the Supporting Materials and Methods, which is published as supporting information on the PNAS web site. ANOVA mixed models have proven successful at analyzing microarray data (41,(44)(45)(46)(47)(48)(49)(50). The array and spot effects were treated as random effects, whereas dye and treatment effect were considered fixed effects.…”
Section: Methodsmentioning
confidence: 99%
“…Raw data were imported into SAS (SAS Institute), compiled, background-corrected, log 2 -transformed, and subjected to a mixed model of analysis of variance (SAS proc mixed) with two sequential linear models (44) outlined in the Supporting Materials and Methods, which is published as supporting information on the PNAS web site. ANOVA mixed models have proven successful at analyzing microarray data (41,(44)(45)(46)(47)(48)(49)(50). The array and spot effects were treated as random effects, whereas dye and treatment effect were considered fixed effects.…”
Section: Methodsmentioning
confidence: 99%
“…It has been difficult to assign function reliably to the PBP components of these because of the distant sequence relationships between T. maritima and biochemically characterized model organisms. A combination of in vitro binding studies (25) and transcriptional expression profiling of cultures grown in the presence of various carbohydrate substrates (26,27) has shown that 5 of 12 PBPs that are homologous to OpBPs bind not oligopeptides but various carbohydrates. The x-ray crystal structure of one of these, the ␤-1,4-mannobiose-binding protein (Protein Data Bank code 1VR5), was recently solved in the open conformation in the absence of its cognate ligand (structure determined and deposited by the Joint Center for Structural Genomics (28) but otherwise undocumented).…”
mentioning
confidence: 99%
“…Probes were designed in OligoArray 2.0 (46), custom synthesized (Integrated DNA Technologies, Coralville, IA), and printed onto arrays following protocols previously developed for other hyperthermophiles (14,20,50); five replicates per probe were spotted on each array to fortify statistical analysis. S. solfataricus was routinely grown at 80°C and pH 4.0 on DSMZ 182 medium; cells were enumerated using epifluorescence microscopy with acridine orange stain (13).…”
mentioning
confidence: 99%